Genome-wide analysis of NBS-LRR genes in Rosaceae species reveals distinct evolutionary patterns - Guo, Liping; You, Chen; Zhang, Hanghang; Wang, Yukun; Zhang, Rui (Frontiers in Genetics, 2022)
The nucleotide-binding site and leucine-rich repeat (NBS-LRR) genes, one of the largest gene families in plants, are evolving rapidly and playing a critical role in plant resistance to pathogens. In this study, a genome-wide search in 12 Rosaceae genomes screened out 2188 NBS-LRR genes, with the gene number varied distinctively across different species. The reconciled phylogeny revealed 102 ancestral genes (7 RNLs, 26 TNLs, and 69 CNLs), which underwent independent gene duplication and loss events during the divergence of the Rosaceae. The NBS-LRR genes exhibited dynamic and distinct evolutionary patterns in the 12 Rosaceae species due to independent gene duplication/loss events, which resulted the discrepancy of NBS-LRR gene number among Rosaceae species. Specifically, Rubus occidentalis, Potentilla micrantha, Fragaria iinumae and Gillenia trifoliata, displayed a “first expansion and then contraction” evolutionary pattern; Rosa chinensis exhibited a “continuous expansion” pattern; F. vesca had a “expansion followed by contraction, then a further expansion” pattern, three Prunus species and three Maleae species shared a “early sharp expanding to abrupt shrinking” pattern. Overall, this study elucidated the dynamic and complex evolutionary patterns of NBS-LRR genes in the 12 Rosaceae species, and could assist further investigation of mechanisms driving these evolutionary patterns.